Experimental and theoretical studies on aqueous-phase reactivity of hydroxyl radicals with multiple carboxylated and hydroxylated benzene compounds1. Issue 17 (7th May 2015) - Minakata, Daisuke; Song, Weihua; Mezyk, Stephen P.; Cooper, William J.
<x xml:space="preserve">Abstract</x> In this study, we shed light on the initial addition of hydroxyl radicals (HO˙) to multiple carboxylated and hydroxylated benzene compounds in aqueous-phase advanced oxidation processes (AOPs).